Investigations of genotoxic activity of antimicrobial/antiviral agent FS-1 in human lymphocytes and tumor cell - Nersesyan, A.; Ilin, A.; Kulmanov, M. (Цитология и генетика, 2011)
A very promising antiviral and antimicrobial agent FS-1 was studied for its ability to induce DNA damage and micronuclei in human tumor cell lines HeLa and Caco-2 at concentrations of 200, 500 and 1000 mg/ml without exogenous metabolic activation. The compound was additionally tested for DNA damaging ability in human lymphocytes at concentrations of 200, 400 and 800 mg/ml. Neither DNA damage nor micronucleus formation was observed after treatment of all types of cells with FS-1. Based on these results, FS-1 can be further studied for its safety to humans for potential application in clinical medicine as an antimicrobial/antiviral drug. Исследовали способность перспективного антивирусного и антибактериального соединения ФС-1 вызывать повреждения ДНК и микроядра в клеточных линиях опухоли человека HeLa и Caco-2 при концентрациях 200, 500 и 1000 мкг/мл без экзогенной метаболической активации. Соединение было дополнительно проверено на ДНК-повреждающую способность в лимфоцитах человека при концентрациях 200, 400 и 800 мкг/мл. Ни повреждения ДНК, ни формирования микроядер не наблюдалось после обработки всех типов клеток ФС-1. На основании этих результатов, ФС-1 может быть далее изучен на предмет безопасности для возможного применения в клинической медицине как антибактериального/противовирусного препарата. Досліджували здатність перспективного противірусного та антибактеріального препарату ФС-1 викликати пошкодження ДНК та мікроядра в клітинних лініях пухлини людини HeLa і Сасо-2 при концентраціях 200, 500 та 1000 мкг/мл без екзогенної метаболічної активації. Препарат був додатково перевірений на ДНК-пошкоджуючу здатність в лімфоцитах людини при концентраціях 200, 400, 800 мкг/мл. Ні пошкодження ДНК, ні формування мікроядер не спостерігалось після обробки всіх типів клітин ФС-1. Базуючись на цих результатах, ФС-1 може далі вивчатись на предмет безпеки для потенційного застосування в клінічній медицині як антибактеріального/противірусного препарату.